Educational Problems in Indonesia - Toni Ardi Rafsanjani; M. Abdur Rozaq (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
Education is one of the most important things in human life. Every human being has the right to receive adequate and equitable education. However, what is happening in Indonesia is the inequality of education for all Indonesian citizens. Apart from that, recently what has been discussed is the education system in force in Indonesia which is considered rigid and ineffective. We can see this from the lagging behind the quality of education in Indonesia compared to other countries. The education system used in Indonesia is not much different from the education systems in other countries. The only difference is mistakes during practice in the field. Many fundamental errors create a gap between the goals of the education system and its implementation in the field. Which ultimately makes all these goals unable to be achieved and completed properly. This research aims to determine the problems of education in Indonesia. The research method used is a qualitative study with a descriptive-analytical approach. The data was collected through in-depth interviews with education stakeholders, including teachers, principals, parents of students, and education experts. The results show that the gap in access to education is still a major problem, especially in remote areas. The uneven quality of education can also be seen in the difference in learning outcomes between schools in urban and rural areas. A curriculum that is not responsive to technological developments and industry needs has also exacerbated this situation. Based on these findings, this study suggests several solutions, including improving educational infrastructure, continuous training for teachers, and revising a more adaptive curriculum.